GAYA KEPEMIMPINAN SERGIUS SARENG SEBAGAI KEPALA DESA, DI DESA WOLOMOTONG, KECAMATAN DORENG, KABUPATEN SIKKA - Kitingan, Yoseph Perin; Tiran, Rex; Kamahi, Syahrin B.; Jacob, Ananias R. P. (SINERGI : Jurnal Riset Ilmiah, 2025)
This study will look at the leadership style of the village head Sergius Sareng during his tenure so that he was again entrusted by the Wolomotong village community to become village head for three periods from 1995-2000 and 2000-2008 and was re-elected as the third period village head in 2022-2028 with 827 votes, out of a total of 1,250 voters. Leadership style is divided into 3 parts, namely participatory leadership style, delegative leadership style, democratic leadership style and transactional leadership as explained earlier that Mr. Sergius Sareng has served as village head for 3 periods for 19 years Sergius Sareng who served as village head can be categorized as successful in leading and bringing about changes in Wolomotong Village such as the construction of the wodonwair road, The construction of 2 SDNs and the mandatory 1 kk realized 80 percent in the field of public health, namely the construction of the wodon wair polindes and the agricultural sector, namely the expansion of nutmeg and vanilla specialty trading crops, the expansion of electricity networks to remote hamlets and RT, RW which made the trust of the Wolomotong Village community even stronger and voted again in the next election period. In his leadership, Sergius Sareng created a good relationship with the village community in the form of fair treatment of all groups of people without discriminating between members of the organization, social and economic status. Good relations in.